Implementasi Strategi Contextual Teaching and Learning dalam Meningkatkan Pemahaman Materi Pendidikan Agama Islam Siswa di SMP Negeri 1 Percut Sei Tuan - Winata, Fatma Ayu; Nasution, Wahyudin Nur (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to examine the implementation of the Contextual Teaching and Learning (CTL) strategy in enhancing students’ understanding of Islamic Religious Education (IRE) material at SMP Negeri 1 Percut Sei Tuan. The background of this research lies in the students' low comprehension of IRE subjects, which are often abstract and lack real-life context. The CTL strategy was chosen because it connects learning material with students' real-world experiences, making learning more meaningful and relevant. This research employed a qualitative approach with a field research design and a phenomenological perspective to explore the experiences of both students and teachers in depth. Data were collected through observation, in-depth interviews, and document analysis. The data analysis technique followed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results of the study indicate that the CTL strategy was effectively implemented through seven core components: constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. Each component was integrated by teachers into the learning process, resulting in increased student engagement and a deeper, contextual understanding of IRE material. Supporting factors included the strong commitment of teachers, institutional support from the school, and students' enthusiasm. On the other hand, obstacles encountered in implementation included limited instructional time and insufficient parental involvement in the learning process at home. The study concludes that the CTL strategy significantly enhances students’ understanding of Islamic Religious Education when applied consistently with comprehensive support from educational stakeholders.